Assignment and Coordination of Autonomous Robots in Container Loading Terminals. Issue 1 (July 2017) - Stavrou, Demetris; Timotheou, Stelios; Panayiotou, Christos G.; Polycarpou, Marios M.
Abstract: The efficient transfer of containers from the storage area to the loading area is an important problem faced in container handling facilities. Although mobile autonomous robots are ideally suited for addressing this problem, their application requires the solution of challenging scheduling and routing problems. In this work, we consider the combined solution of such problems in a specific setting which exhibits unique characteristics in terms of topology configuration and movement freedom, introducing new challenges. We use the concept of Abstract Time-Windows to represent the movement of the robots and define the conditions and operations necessary for detecting and resolving conflicts between the robots. We develop a low-complexity heuristic approach that provides fast, close-to-optimal solution to the problem. Performance evaluation demonstrates that the heuristic approach generates solutions within 5% of the optimal solution while executing six orders of magnitude faster.